Cardiomyocyte fusion as a new mechanism contributing to pathological cardiac hypertrophy. (10th June 2022) - Colliva, A; Vodret, S; Bongiovanni, W; Zacchigna, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Pathological cardiac hypertrophy is a maladaptive remodeling response, induced by multiple pathogenetic mechanisms, including genetic mutations and hypertension. Despite the high prevalence of this condition, the precise mechanisms driving its onset and progression remain elusive. Recent evidence indicates that homotypic cell fusion between cardiomyocytes occurs in the heart of lower vertebrates in response to injury, as well as in the rodent heart during the first week after birth, when cardiomyocyte size and ploidy increase. We hypothesized that homotypic fusion of cardiomyocytes could be triggered by pressure overload and contribute to cardiac hypertrophy. Methods and Results: We exploited a genetic mouse model (MHC-CreER/mTmG mice) to genetically label individual cardiomyocytes by either red or green fluorescence. These mice express a tamoxifen inducible Cre recombinase (CreER) under the control of the myosin heavy chain 6 promoter (MHC). Controlled injection of tamoxifen resulted in a mosaic heart, composed by either red or green cardiomyocytes. In this genetic background, we performed transverse aortic constriction (TAC) to induce cardiac hypertrophy and analyzed cardiomyocyte size and fluorescence at one month. The systematic analysis of more than 5000 cardiomyocytes from 6 independent experiments showed a significant increase in the number of yellow cardiomyocytes after TAC compared to sham hearts, consistent with cell-cell fusion events occurred between green and red cardiomyocytes. Moreover, these yellow hypertrophic cardiomyocytes displayed a higher rate of polynucleation, with many cells bearing three or more nuclei. Conclusions and future perspective: Collectively, these data point to cardiomyocyte fusion as a new mechanism responsible for to the onset of cardiac hypertrophy upon pressure overload. We cannot exclude that yellow, polynucleated cardiomyocytes derived from the heterotypic fusion between a green cardiomyocyte and other red cell types. To rule out this possibility we are currently performing a new a set of experiments in which 100% of cardiomyocytes are labelled in green. In the case of homotypic fusion, we should not observe any yellow cells upon TAC. Proving that cardiomyocyte fusion contributes to cardiac hypertrophy in response to increased pressure load and dissecting the underlying molecular mechanisms will pave the way to novel strategies to both prevent and revert this highly prevalent pathological condition.